2022
DOI: 10.1155/2022/2517250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Coupling Effect of Thermal and Traffic Loads on Cement Concrete Pavement with Voids Repaired with Polymer Grout

Abstract: Under the repeated action of traffic and thermal loads, a cement concrete pavement slab may partially lose contact with its base course, and voids may develop underneath the slab. Such distress will greatly impact the pavement performance. To fill the voids and restore the base support to the slab, the technology of polymer grouting has been increasingly adopted in recent years due to its advantages of quick application and high efficiency. There is, however, a lack of research on the mechanistic responses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Moreover, the pattern of stress increase is influenced by the existing high temperature. This pattern is similar to that of the research conducted by Cui et al (2022) and El-nakib (2007).…”
Section: Vehicle Load Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the pattern of stress increase is influenced by the existing high temperature. This pattern is similar to that of the research conducted by Cui et al (2022) and El-nakib (2007).…”
Section: Vehicle Load Analysissupporting
confidence: 90%
“…The research carried out by Cui et al (2022) assessed the thermal stress response of rigid pavements that have bottom voids with polymer grout fillers in the time domain, and the design traffic load was employed. A finite element method with a 3-dimensional approach with the help of Abaqus was also used.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, rigid polyurethane foam (RPUF) is a polyurethane foam that does not undergo significant deformation under a certain load and cannot return to its initial state when deformation occurs under excessive load. In recent years, RPUF materials have been widely used in water conservancy [ 12 ], civil engineering [ 13 ], transportation [ 14 , 15 ], and mining [ 16 , 17 ] because of the advantages of no maintenance, fast reaction molding, lightweight, and good mechanical properties, etc. Its main role in water conservancy projects is to replace some cement-based materials with polyurethane foam materials as grouting materials for foundation treatment [ 18 ] and seepage control and repair [ 19 , 20 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al showed through experiments that polymers can efectively repair the settlement of high-speed railways and provide sufcient long-term durability under dynamic train loads [19,20]. Te research of Li et al shows that high polymer can efectively repair cracks and voids in pavement and efectively prevent pavement settlement [21,22]. Te polymer grouting material can sufciently and densely fll the damaged area, thereby controlling the unfavorable deformation and better restoring the structural integrity.…”
Section: Introductionmentioning
confidence: 99%